Analisis Kepuasan Karyawan Yang Dipengaruhi Model Kepemimpinan Transformasional Dan Pemberian Insentif (Studi Pada Karyawan Pt. Telkom Akses Gorontalo) - Rahman, Endi; Machmud, Rizan; Rhomadona, Intan (JURNAL MANAJEMEN PENDIDIKAN, 2025)
ANALYSIS OF EMPLOYEE SATISFACTION INFLUENCED BY TRANSFORMATIONAL LEADERSHIP MODELS AND INCENTIVE PROVISION (STUDY ON EMPLOYEES OF PT. TELKOM ACCESS GORONTALO)This study aims to determine: (1) the influence of transformational leadership on employee satisfaction, (2) the influence of incentive provision on employee satisfaction; and (3) the simultaneous influence of transformational leadership and incentive provision on employee satisfaction. The study employed a descriptive quantitative method analyzed through multiple linear regression, with data processed using IBM SPSS. The study population consisted of 130 employees, and the sample comprised 39 respondents selected through the distribution of an offline questionnaire. The findings indicate that: (1) transformational leadership has a significant influence on employee satisfaction, as shown by the t-count being greater than the t-table value (6.589 1.684); (2) incentive provision also has a significant influence on employee satisfaction, supported by the t-count exceeding the t-table value (6.589 ≥ 1.684); and (3) simultaneously, transformational leadership and incentive provision significantly influence employee satisfaction, as evidenced by the F-test result (F-count 52.579 3.24) at a 5% significance level. The R-squared value obtained is 0.745, indicating that transformational leadership and incentive provision collectively account for 74.5% of the variance in employee satisfaction, whereas the remaining 25.5% is influenced by other variables not examined in this study, such as work environment, conflict management, and organizational culture.